2021
DOI: 10.1039/d1fo01073e
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin enhances the membrane trafficking of the sodium iodide symporter and augments radioiodine uptake in dedifferentiated thyroid cancer cells via suppression of the PI3K-AKT signaling pathway

Abstract: Radioactive iodine (RAI) is commonly used to treat differentiated thyroid cancer (DTC). A major challenge is dedifferentiation of DTC with the loss of radioiodine uptake. Patients with distant metastases have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Besides, several factors, including blockade of phosphatidylinositol glycan anchor biosynthesis class U (PIGU) by activating an MAPK signaling pathway, increased leukemia-associated RhoA guanine exchange factor (LARG) owing to PTEN deficiency, induction of NIS proteolysis by valosin-containing protein as a component of endoplasmic reticulum-associated degradation, and overexpression of pituitary tumor-transforming gene 1 (PTTG1)-binding factor (PBF), have been shown to trigger impairment of NIS membrane targeting [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. On the other hand, recognition of ADP-ribosylation factor 4 (ARF4) by VAPK motif in the NIS C-terminus, regulation of SRC/RAC1/PAK1/PIP5K/EZRIN pathway, activation of RAC1 via MAPK inhibition, application of transient receptor potential vanilloid type 1 (TRPV1) agonist and others were shown to promote NIS functionality and trafficking towards the cell membrane [ 41 , 42 , 43 , 44 , 45 ]. Recently, an article suggested the role of protospacer adjacent motif (PDZ)—PDZ interaction which means PDZ-domain containing protein SCRIB binds to the carboxy-terminus of NIS to localize at proper basolateral plasma membrane [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several factors, including blockade of phosphatidylinositol glycan anchor biosynthesis class U (PIGU) by activating an MAPK signaling pathway, increased leukemia-associated RhoA guanine exchange factor (LARG) owing to PTEN deficiency, induction of NIS proteolysis by valosin-containing protein as a component of endoplasmic reticulum-associated degradation, and overexpression of pituitary tumor-transforming gene 1 (PTTG1)-binding factor (PBF), have been shown to trigger impairment of NIS membrane targeting [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. On the other hand, recognition of ADP-ribosylation factor 4 (ARF4) by VAPK motif in the NIS C-terminus, regulation of SRC/RAC1/PAK1/PIP5K/EZRIN pathway, activation of RAC1 via MAPK inhibition, application of transient receptor potential vanilloid type 1 (TRPV1) agonist and others were shown to promote NIS functionality and trafficking towards the cell membrane [ 41 , 42 , 43 , 44 , 45 ]. Recently, an article suggested the role of protospacer adjacent motif (PDZ)—PDZ interaction which means PDZ-domain containing protein SCRIB binds to the carboxy-terminus of NIS to localize at proper basolateral plasma membrane [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, curcumin has the ability to enhance NIS glycosylation and facilitate its membrane transport, resulting in notable enhancements in vitro radioactive iodine uptake. And it can enhance radioiodine sensitivity by inhibiting the PI3K-AKT-mTOR signaling pathway ( Zhang L. et al, 2021b ). RAI therapy, widely employed in thyroid cancer, frequently induces impaired salivary gland dysfunction.…”
Section: Promising Natural Products For the Treatment Of Thyroid Cancermentioning
confidence: 99%
“…In in vitro and in vivo studies of thyroid cancer, NPs have shown good therapeutic potential. Numerous studies have demonstrated that various natural compounds derived from food and herbs possess the ability to inhibit TC, including inhibiting the occurrence and development of TC ( Yu et al, 2013 ; Hong et al, 2021 ; Lu et al, 2022 ), promoting redifferentiation of poorly differentiated TC ( Lakshmanan et al, 2015 ; Zhang L. et al, 2021b ), alleviating TC drug treatment resistance ( Li et al, 2018 ; Bian et al, 2020 ; Celano et al, 2020 ), and so on. Previously, my research group published basic research on tangeretin and nobiletin.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting major signaling pathways such as protein 53, nuclear factor-κB (NF-κB), and phosphoinositide-3-kinase/AKT serine-threonine kinase/ mechanistic target of the rapamycin kinase signaling pathways could restore the efficiency of radioiodine sensitivity in PTC cells. [16][17][18] Pyruvate kinase M2 (PKM2), a key rate-limiting enzyme of glycolysis, is universally expressed during embryogenesis, tissue repair, and cancer. 19 Human tumors, including breast and colon cancers, express high levels of PKM2, which promotes the Warburg effect.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanisms revealed that several factors were related to the decreased efficiency of radioiodine therapy in PTC. Targeting major signaling pathways such as protein 53, nuclear factor‐κB (NF‐κB), and phosphoinositide‐3‐kinase/AKT serine–threonine kinase/mechanistic target of the rapamycin kinase signaling pathways could restore the efficiency of radioiodine sensitivity in PTC cells 16–18 …”
Section: Introductionmentioning
confidence: 99%